2023
DOI: 10.1038/s41598-023-35093-9
|View full text |Cite
|
Sign up to set email alerts
|

A novel deep learning approach for typhoon-induced storm surge modeling through efficient emulation of wind and pressure fields

Abstract: Modeling typhoon-induced storm surges requires 10-m wind and sea level pressure fields as forcings, commonly obtained using parametric models or a fully dynamical simulation by numerical weather prediction (NWP) models. The parametric models are generally less accurate than the full-physics models of the NWP, but they are often preferred owing to their computational efficiency facilitating rapid uncertainty quantification. Here, we propose using a deep learning method based on generative adversarial networks (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 48 publications
(57 reference statements)
0
4
0
Order By: Relevance
“…While numerical models require more computation resources and time to update the forecasts in real-time forecasting. Mulia et al [139] showed that the computation time for a 73-h simulation for GAN and parametric model is 13 s and 8 s, respectively, with a single processor, while that for a 45-h simulation of NWP is 4200 s on a supercomputer with 256 processors. Though during the training phase, ML models can also be computationally expensive, especially when the model architecture is more sophisticated and dealing with large datasets, ML models are more efficient, especially for site-specific forecasting as a whole.…”
Section: When Does ML Perform Better Than Traditional Methods?mentioning
confidence: 99%
See 2 more Smart Citations
“…While numerical models require more computation resources and time to update the forecasts in real-time forecasting. Mulia et al [139] showed that the computation time for a 73-h simulation for GAN and parametric model is 13 s and 8 s, respectively, with a single processor, while that for a 45-h simulation of NWP is 4200 s on a supercomputer with 256 processors. Though during the training phase, ML models can also be computationally expensive, especially when the model architecture is more sophisticated and dealing with large datasets, ML models are more efficient, especially for site-specific forecasting as a whole.…”
Section: When Does ML Perform Better Than Traditional Methods?mentioning
confidence: 99%
“…In terms of timeliness, an operational forecast usually can give a longer forecast horizon of over 72 h. However, the forecast horizons of ML models are usually up to 12 h ahead [10,49,102,139,149]. Only a small part of studies extended the lead time to 24 h [44,83], and fewer studies attempted to output the forecast water level time series with a length of over 24 h [38,48,62,78,79].…”
Section: When Does ML Perform Better Than Traditional Methods?mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover Machine learning offer a clear advantage in capturing the nonlinear interactions between typhoon influencing factors and storm surge magnitude. These models necessitate a one-time investment in training time, enabling swift forecasting using the pre-trained model, thus promoting widespread adoption (Tadesse et al, 2020;Ayinde et al, 2023;Ku and Liu, 2023;Li et al, 2023;Mulia et al, 2023). Ayyad et al (2022a) employed a coupled ADCIRC and SWAN model to generate a dataset comprising 10,300 typhoon-induced storm surge events.…”
mentioning
confidence: 99%